Molecular magnesium hydrides supported by an anionic triazacyclononane-type ligand. Issue 6 (25th January 2017) - Schnitzler, S.; Cui, P.; Spaniol, T. P.; Okuda, J.
Abstract : A dimeric magnesium hydride supported by a monoanionic TACN-type ligand is formed by an unusual rearrangement of an unstable mononuclear complex with a terminal Mg–H bond. Abstract : Molecular magnesium hydride with a terminal metal–hydrogen bond [Mg(iPr2 TACN·AliBu3 )H]2 supported by a monoanionic TACN-type ligand (TACN = 1, 4-di-isopropyl-1, 4, 7-triazacyclononane) rearranges to form the dinuclear magnesium hydride [Mg(iPr2 TACN·AlHiBu2 )(μ-H)]2, exhibiting a rare Mg⋯H–Al interaction.